PENERAPAN RESTORATIVE JUSTICE TERHADAP ANAK SEBAGAI PELAKU TINDAK PIDANA ASUSILA DALAM PERSPEKTIF UNDANG – UNDANG NOMOR 17 TAHUN 2016 TENTANG PERUBAHAN KEDUA ATAS UNDANG –UNDANG NOMOR 23 TAHUN 2002 TENTANG PERLINDUNGAN ANAK (Analisa Putusan No. 49/Pid.Sus-Anak/2019/PN. Tng) - M. Aidil Aidil (Rechtsregel : Jurnal Ilmu Hukum, 2020)
Through this article, the author has carried out work on restorative justice, which can be a guide and concern in the pursuit of justice and the safety of children in particular. The rise in criminal acts of sexual abuse committed by children has been very serious in recent times. In compliance with the rules of the existing laws and regulations, law enforcement agencies are obliged to pursue diversion for children who are engaged in a criminal act but, in particular, for children who have committed a criminal act of fornication, no effort can be made at diversion. A child who performs a criminal act of sexual immorality shall be prosecuted in compliance with the laws in effect. In the case of children as victims of sexual immorality, it is definitely not easy to agree on criminal penalties against them, considering that they are children who also have the right to grow up and develop. The Law of the Republic of Indonesia No 35 of 2014 on the Protection of the Child and the Law of the Republic of Indonesia No 11 of 2012 on the Child Criminal Justice System was also adopted in order to safeguard and secure the interests of children in conflict with that rule. The authors used qualitative descriptive methods and normative approaches in this study and included case examples to make it easier to analyze and contribute to legal remedies.